The Role of Debate Learning in Improving Students' Critical and Argumentative Thinking Skills: A Needs Analysis - Hendra Kurnia Pulungan; Dadang S Anshori; Sumiyadi Sumiyadi; Yeti Mulyati (Universitas Muhammadiyah Malang, 2025)
This study aims to analyse the role of debate learning in improving students' critical and argumentative thinking skills. Debate learning is an effective method to train analytical thinking skills and craft strong arguments. However, understanding the extent to which debate learning affects this ability in students is still limited. This research uses a qualitative approach with a needs analysis method to explore students' experiences and views related to debate learning. Data was obtained through interviews and documentation studies involving students from various departments. The results show that learning debate significantly improves students' critical thinking skills, allows them to be more open to accepting different opinions, and strengthens their ability to build logical and structured arguments. In addition, this study also found that debate learning positively impacts the development of students' communication and persuasion skills. In conclusion, debate learning has an important role in improving the quality of students' critical and argumentative thinking, so it can be an effective method in higher education to prepare students to face challenges in the professional world.